Sexual Harassment of Women at Workplace – A Legal Myth - Deva, Shraddha (JOURNAL OF INDIAN EDUCATION, 2014)
Our Constitution enshrines equality as one of the basic features; despite that woman in India is a disadvantaged lot who suffers violation of her rights based on gender. Sexual harassment of women at workplace is one such form of violation of her rights. This problem has its roots embedded in the patriarchal nature of our society. Parliament has recently enacted a law to counter the menace, seventeen years later the guidelines issued by the Honourable Supreme Court in Vishakha case. This paper studies the problem of sexual harassment in Kendriya Vidyalayas situated in the city of Agra. The paper attempts to provide some important insights in the form of observations and recommendations and finally concludes with an outcome that law can be implemented effectively only when there is a scope for change in attitude of the citizens of a country.